The Impact of Dr. Mahmūd Aḥmad Ghᾱzῑ on Contemporary Styles and Practices in Sirah Writing: A Research Based Study - Dr. Abdul Muhaimin; Anila Mustafa (Seerat Studies, 2023)
This research has primarily focused on the modern approaches and methodologies in Sīrah writing highlighting the valuable contributions of late Dr. Mahmūd Aḥmad Ghᾱzῑ. The study contains various old and modern approaches and methodologies of Sīrah writing explained in connection with diverse innovative issues. It is now more than fourteen hundred years that Sīrah is being written. Various ages and varying political conditions had its effects on different approaches and methodologies of Sīrah writings. The life of the Prophet has been discussed in the perspective of the upcoming challenges as well. Like other fields of Islamic studies, the Sīrah writing has also been expanded to great extent in terms of its trends. New approaches and methodologies are introduced in Sīrah writing which are more in line with the needs of the time. The study has also focused on various approaches and methodologies in Sīrah studies developed and evolved mainly in twentieth century.